Identification of Sox8 as a modifier gene in a mouse model of Hirschsprung disease reveals underlying molecular defect. - Wegner, Michael; Stolt, Claus; et al. (Developmental Biology, 2005)
Mice carrying heterozygous mutations in the Sox10 gene display aganglionosis of the colon and represent a model for human Hirschsprung disease. Here, we show that the closely related Sox8 functions as a modifier gene for Sox10-dependent enteric nervous system defects as it increases both penetrance and severity of the defect in Sox10 heterozygous mice despite having no detectable influence on enteric nervous system development on its own. Sox8 exhibits an expression pattern very similar to Sox10 with occurrence in vagal and enteric neural crest cells and later confinement to enteric glia. Loss of Sox8 alleles in Sox10 heterozygous mice impaired colonization of the gut by enteric neural crest cells already at early times. Whereas proliferation, apoptosis, and neuronal differentiation were normal for enteric neural crest cells in the gut of mutant mice, apoptosis was dramatically increased in vagal neural crest cells outside the gut. The defects in enteric nervous system development of mice with Sox10 and Sox8 mutations are therefore likely caused by a reduction of the pool of undifferentiated vagal neural crest cells. Our study suggests that Sox8 and Sox10 are jointly required for the maintenance of these vagal neural crest stem cells. © 2004 Elsevier Inc. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2005.med.IB.LPCIPDBI.identi
Keywords: Enteric nervous system; High-mobility-group; Hirschsprung disease; Megacolon; Sox10; Sry